PREVALENSI HERPES ZOSTER DI POLI KLINIK KULIT DAN KELAMIN RUMAH SAKIT PERTAMEDIKA UMMI ROSNATI BANDA ACEH - Rizky Kurniawan; Vivi Humaira (Jurnal Sains Riset, 2021)
Herpes Zoster is a contagious disease caused by reactivation of varicella-zoster virus (VZV).  It is reported that the prevalence of this disease in America is up to 1,000,000 cases per year, with the incidence of 1,2 to 4,8 cases per 1000 people per year. Therefore, the prevalence of herpes zoster from 13 educational hospitals in Indonesia from 2011-2013 reaches 2,232 cases. Meanwhile, the data from Ummi Rosnati Pertamedika Hospital in Banda Aceh indicates that out of 3,595 patients, 26 of them are identified as having herpes zoster. Based on this data, this study aims to investigate the prevalence of herpes zoster in the Skin and Genital Polyclinic of Ummi Rosnati Pertamedika Hospital, Banda Aceh. This research was a descriptive retrospective study with a cross-sectional design.  This study was conducted from April to June 2019. The population was all the patients in Ummi Rosnati Hospital. The sample was 26 patients chosen by using an accidental sampling technique. Then the data were analyzed by using SPSS. The results showed that based on the age category, the prevalence of herpes zoster mostly occurs among the elderly 53,8% (14 patients).  Further, the findings also indicated that based on the gender category, the cases of herpes zoster mostly found on males 65,4% (17 patients) and females 34,6% (9 patients). While the prevalence of herpes zoster based on patients’ job was indicated that around 11 patients are from private sectors (42,3%) and the rest of the patients are housewives 26,9% (7 patients). Overall, the prevalence of herpes zoster based on the medical history indicated that all 26 or 100% of patients are having varicella disease history. From these findings,  it is hoped that this study can provide valuable information to improve the knowledge on how to handle the herpes zoster as a way to improve the health level, especially towards herpes zoster.Keywords: Prevalence, Herpes Zoster, Varicella Zoster Virus (VZV)